A global synthesis of the impacts of urbanization on bird dawn choruses. (4th May 2021) - Marín‐Gómez, Oscar H.; MacGregor‐Fors, Ian
Abstract : Urbanization drives changes in acoustic communication systems in some animal species. Noise and light pollution are among the main urban factors known to disrupt the timing and structure of avian singing behaviour. Despite our understanding of the ways in which urbanization can drive variations in avian acoustic communication, our ability to generalize the underlying causes of such variation and its consequences is still limited. Here, we reviewed the literature focused on the study of avian dawn choruses in urban settings at a global scale. Our findings reveal that avian dawn chorus research has focused on the impact of anthropogenic noise on dawn chorus traits (i.e. timing, peak, song output, song frequencies); relationships between light pollution and chorus timing; the effects of temperature, cloudiness, moonlight and natural light on chorus timing; relationships between nocturnal noise and light, and dawn chorus timing; the effects of chemical pollution and supplementary feeding on dawn chorus activity; and ecological patterns of dawn choruses in soundscapes across urban–non‐urban gradients. We identified important knowledge gaps in the study of avian dawn choruses in urban settings and thus suggest future research directions, including frameworks (e.g. the urbanization intensity gradient) and consideration of a wider array of urban conditions and variables. Given the complexity of urban settings, we encourage further studies to address the role that all sources of pollution can have on avian acoustic communication at dawn. Additionally, a central question to resolve is whether the function of avian dawn choruses in urban areas differs, and if so how, from non‐urban counterparts. Given that most research has been performed across Holarctic cities and towns, studies from tropical and subtropical regions are needed if we aim to understand the phenomenon globally. Finally, studies at the community‐ and soundscape‐level across cities could advance understanding of the way in which urban birds use the acoustic space during the most critical singing time period, dawn.